Diffusion-Weighted MR Imaging in a Rat Model of Syringomyelia after Excitotoxic Spinal Cord Injury - Schwartz, Eric D.; Yezierski, Robert P.; Pattany, Pradip M.; Quencer, Robert M.; Weaver, Raymond G. (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Recent experimental data have shown that an increase of excitatory amino acids and the initiation of inflammatory responses within the injured spinal cord may play a role in post-traumatic syringomyelia. The purpose of this study was to determine whether diffusion-weighted MR imaging with apparent diffusion coefficient (ADC) maps could provide earlier evidence of spinal cord cavitation in a rat model of syringomyelia than available with conventional MR imaging.METHODS: The spinal cord gray matter of four rats was injected with the α-amino-3 hydroxy-5 methyl-4 isoxazole propionic acid/metabotropic receptor agonist quisqualic acid. Animals were sacrificed at 1, 4, or 8 weeks after injection, and the spinal cords were fixed in formalin for 1 week and imaged with T1-, T2-, and diffusion-weighted sequences. One control specimen was also imaged. ADC maps were constructed from the diffusion-weighted data. Histopathologic analyses of sections stained with cresyl violet were compared with the MR images.RESULTS: By 1 week after injection, ADC maps at the level of injection showed areas within the gray matter of increased intensity and increased ADC values as compared with the control specimen. These bright areas corresponded to cysts or cavities within the cord parenchyma on the histopathologic sections. The ADC values within affected gray matter areas progressively increased at 4 and 8 weeks, also corresponding to cyst formation. Conventional T1- and T2-weighted images showed corresponding lesions with cystic characteristics at 4 and 8 weeks, but not at 1 week.CONCLUSION: In an animal model of syringomyelia, diffusion-weighted imaging with ADC maps detected cystic lesions within spinal cord gray matter before they were seen on conventional T1- and T2-weighted images.